2015
DOI: 10.1074/jbc.m115.649582
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-B Cell Receptor Complexes Associate with Intracellular major histocompatibility complex (MHC) Class II Molecules

Abstract: Background: Mechanisms that preferentially deliver B cell receptor-antigen complexes to receptive MHC class II molecules are poorly defined. Results: Internalized B cell receptor-antigen complexes associate with class II molecules. Conclusion: In B cells, B cell receptor-antigen complexes associate with peptide-loaded class II molecules, potentially defining sites of class II ligand acquisition. Significance: Antigen-specific B cells control the loading of cognate antigen-derived peptide onto class II molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…More recently, we extended the initial structural studies of King and Dixon (King and Dixon, 2010) and identified two I-A k class II conformers that differ in pairing of transmembrane (TM) domain GxxxG dimerization motifs [Figure 1, (Dixon et al, 2014)]. Moreover, we have demonstrated that while M1 paired class II molecules numerically represent ~10% of cell surface class II, they can carry greater than 90% of MHC class II function (Barroso et al, 2015; Busman-Sahay et al, 2011; Sprent et al, 1981). We have also established that M1 paired class II are enriched in plasma membrane lipid rafts (Busman-Sahay et al, 2011), have unique signaling properties (Nashar and Drake, 2006) and are selectively incorporated into a putative MHC class II peptide loading complex where cognate antigen bound to the BCR is converted into peptide bound to M1 paired class II (Barroso et al, 2015).…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…More recently, we extended the initial structural studies of King and Dixon (King and Dixon, 2010) and identified two I-A k class II conformers that differ in pairing of transmembrane (TM) domain GxxxG dimerization motifs [Figure 1, (Dixon et al, 2014)]. Moreover, we have demonstrated that while M1 paired class II molecules numerically represent ~10% of cell surface class II, they can carry greater than 90% of MHC class II function (Barroso et al, 2015; Busman-Sahay et al, 2011; Sprent et al, 1981). We have also established that M1 paired class II are enriched in plasma membrane lipid rafts (Busman-Sahay et al, 2011), have unique signaling properties (Nashar and Drake, 2006) and are selectively incorporated into a putative MHC class II peptide loading complex where cognate antigen bound to the BCR is converted into peptide bound to M1 paired class II (Barroso et al, 2015).…”
Section: Introductionmentioning
confidence: 63%
“…The plasmids were transfected into CIITA expressing 293T cells as previously reported (Busman-Sahay et al, 2011; Dixon et al, 2014). 24-48 hour culture supernatants were collected, cleared of debris by centrifugation and then analyzed by immunoprecipitation with either the 10-3.6 or 11-5.2 mAb and western blot with a rabbit antibody specific for a peptide derived from the Aβk extracellular domain (Barroso et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interaction of internalized BCR/antigen with intracellular MHCII was observed in pulldowns using biotin-labeled antigen (78). Strikingly, a rare (10%) conformation of MHCII seems to be a predominant conformer in complex with the BCR/antigen.…”
Section: Internalization Of Bcr and Intersection With Mhcii In The Mhmentioning
confidence: 99%